2001
DOI: 10.1055/s-2001-9750
|View full text |Cite
|
Sign up to set email alerts
|

Fused Quinoline Heterocycles IV: First Synthesis of Four Heterocyclic Ring Systems of 1H-5-Thia-1,2,3,6-Tetraazaacephenanthrylenes and 1H-5-Thia-1,3,6-Triazaacephenanthrylenes

Abstract: Reaction of 4-alkylamino-2-chloroquinoline-3-carbonitriles 4a-e with an equimolecular amount of ethyl mercaptoacetate gave, in each case, the corresponding ethyl 4-alkylamino-3-aminothieno[2,3-b]quinoline-2-carboxylates 7a-e. Diazotization of 7a-e afforded the novel tetracyclic ring system ethyl 1-alkyl-1H-5-thia-1,2,3,6-tetraazaacephenanthrylene-4-carboxylates 8a-e. Refluxing 7a-e with an excess of triethyl orthoformate yields the new ethyl 1-alkyl-1H-5-thia-1,3,6-triazaacephenanthrylene-4-carboxylates 9a-e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…6 In fact, the synthesis and the activity of a number of natural products with fused quinoline heterocyclic skeletons have been reported. 7 In particular, we considered that the thiazole moiety, which is present in a number of important natural products (epothilone, 8 althiomycin, 9 bistramide C, 10 sulfomycin I 11 ), in antibiotics (cystothiazole 12 ) and, notably, in thiamine (vitamin B) inter alia, would be an interesting and promising substructure to be included in our target molecules.…”
Section: Methodsmentioning
confidence: 99%
“…6 In fact, the synthesis and the activity of a number of natural products with fused quinoline heterocyclic skeletons have been reported. 7 In particular, we considered that the thiazole moiety, which is present in a number of important natural products (epothilone, 8 althiomycin, 9 bistramide C, 10 sulfomycin I 11 ), in antibiotics (cystothiazole 12 ) and, notably, in thiamine (vitamin B) inter alia, would be an interesting and promising substructure to be included in our target molecules.…”
Section: Methodsmentioning
confidence: 99%
“…CH), 1700 (CO, ester), 1680 (CO, amide) cm -1 ; 1 H NMR (DMSO-d 6 ): δ = 1.39 (t, 3H, J = 7Hz, CH 3 ), 1.49-1.67 (m, 8H, H aliph ), 2.16 (m, 2H, H aliph ), 2.28 (s, 3H, CH 3 ), 4.30 (br, 1H, H aliph ), 4.43 (q, 2H, J = 7Hz, CH 2 ), 7.0 (s, 2H, NH 2 ), 7.20 (t, 1H arom , J = 8Hz), 7.52 (t, 1H arom , J = 8Hz), 7.69 (d, 1H arom , J = 8Hz), 7.81 (d, 1H arom , J = 8Hz), MS: m/z (%) = 411 (M + , 19), 364 (2), 329 (100), 314 (78), 287 (23), 286 (11), 266 (19), 252 (18), 239 (22), 215 (30), 197 (13), 128 (7), 82 (2), 55 (25).…”
Section: Tetrazoloquinolinesmentioning
confidence: 99%
“…For some time, our research has focused on the synthesis of fused heterocyclic systems, particularly those containing a quinoline nucleus, with the aim of evaluating their pharmacological and/or biological activity [4][5][6][7]. As a result of this work, we recently reported a new and useful method for the synthesis of novel tetracyclic ring systems [8][9][10][11][12]. In pharmacological studies thieno[3,4-d]-pyrimidines have been shown to possess pharmacological activities including antibacterial [13], antihypertensive [14,15], antiulcer [16], fungicidal [17], gastric acid secretion inhibitory [18], insecticidal, miticidal [17] vasodilatory [14] activity, and antiallergic activity [19].…”
mentioning
confidence: 99%
“…Quinolines annulated to other heterocycles have recently drawn much attention, due to their considerable pharmacological and biological activities In this context, thienoquinolines are of considerable current interest as they possess anti‐bacterial, anti‐inflammatory and anti‐tumor properties . Moreover, they are immunoregulators, drug resistance modulators, memory enhancers, as well as analgesics and antipyretics , . The quinolone substructure, contained in thienoquinolones, shows many of the attributes of an ideal antibiotic, combining high potency, a broad spectrum of activity, good bioavailability and a potentially low incidence of side‐effects .…”
Section: Introductionmentioning
confidence: 99%